Knowledge Management, Organizational Innovativeness, and Adversity Quotient on Institutional Performance of Local Economic Enterprises - Eduardo C. Delgado Jr (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study attempted to assess the influence of knowledge management, organizational innovativeness, and adversity quotients manifested through the institutional performance. There are 221 local economic enterprise employees of the local government units in Bukidnon participated in the study, which employed a quantitative descriptive design, to evaluate the relationship between two or more variables as well as the multiple regression analysis in determining variables that predict institutional performance. Findings revealed that knowledge management, organizational innovativeness, and adversity quotient are predictors, positively correlated and have a statistically significant relationship to institutional performance. The overall predictive model is presented as follows; Institutional performance = 1.123 + 0.189*Ownership. The overall model tested was highly significant with F = 3.654, p=.000. The regression model further discloses that for every unit change in ownership, there is a corresponding increase by .189 of the institutional performance. Based on this result, the null hypothesis is rejected. The independent variable, taken as a whole, can predict the institutional performance of the local economic enterprise employees. The data implies that the higher level of ownership in adverse situations of the local economic enterprise employees, the more they have performed well in their institutional performance. Therefore, one of the practical implications of this result in the management of organizational innovation processes is that to manage the innovation process effectively, owners and, or managers need to understand knowledge management and innovativeness factors that affect different innovation types in their institutional performance.